Effects of Lithospheric Properties on Crustal Strain at Both Ends of Longmen Shan Orogenic Belt: Based on Numerical Simulation - Shen, Tuo; Xu, Xiwei; Li, Yujiang; Huang, Luyuan; Rogozhin, E. A.; Wang, Qixin; Kang, Wenjun; Lei, Xiaoqiong (Frontiers in Earth Science, 2022)
Strain partitioning and accommodation are fundamental constraints to evaluate tectonic models of orogenic plateaus. The uplift mechanism issue of the eastern Tibetan Plateau has remained a long-term focus since the last century, namely, the steep uplift of the Longmen Shan area. Several tectonic models have been proposed to describe the uplift process of the central Longmen Shan area along the eastern margin of the Tibetan Plateau. Such as upper crustal shortening, mid-crustal channel flow, and whole-crust shearing. However, these models are typically examined through vertical differences. Geophysical, geological, remote sensing and geochemistry observation data indicate that there occur not only vertical differences but also obvious horizontal differences along the Longmen Shan orogenic belt. Based on the finite element method, we employed two-dimensional profiles crossed northern and southern Longmen Shan fault to reconstruct the uplift process of the Longmen Shan orogenic belt. The mechanical properties of the lithosphere south of the Longmen Shan orogenic belt were slightly less favorable than those of the lithosphere north of the Longmen Shan orogenic belt. For the better fitting result in the southern part viscosity of lower crust is less than 1021 Pa∙s and in the northern part viscosity of lower crust is around 1022 Pa∙s. The uplift processes in the upper and lower crust of the Longmen Shan orogenic belt were partially decoupled. The deformation of lithosphere in the northern Longmen Shan orogenic belt is smaller than it in southern Longmen Shan orogenic belt. Due to that the rigid Ruoergai block maybe resists the formation of a weak layer or enters of weak materials to the northern Longmen Shan block, resulting in the observed difference in lithospheric properties between the northern and southern Longmen Shan blocks.